Balance Training And Their Effect On Momentum and Torque In Different Phases Of Passing and Achievement in 110m Youth Hurdles - Rasheed, Intisar (Journal of Physical Education, 2017)
The importance of the research lies in static and dynamic balance during athletic performance. Balance is affected by external forces thus the researcher aimed at using balance training using tools on 110 m hurdlers and finding its effect on momentum and torque in the different phases of passing the 1–5–10 hurdles especially biomechanical variables